MAPEAMENTO DE PROCESSOS NA GESTÃO DA CONSTRUÇÃO CIVIL UTILIZANDO A TEORIA DAS RESTRIÇÕES - Macarini, Jonathan Willian; Dalmolin, Michael Valmor; Santos, Rúbia Bernadete Pereira dos (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In order to improve the efficiency and effectiveness of companies, in the building industry - ICC, it is necessary to act more consistently as the processes of implementation of the quality management system. In this context, the objective of this article was to elaborate a management model of ICC administrative processes, based on the theory of constraints - TOC. In order to increase the capacity of the company and ensure compliance with the regulatory requirements of the Quality Management System. A research was carried out, where the processes of planning, control and execution of works, acquisition of materials, services and equipment, receipt and inspection of materials and services and human resources were analyzed. After analysis, the mapping of each process was generated and from the same it was compatibilized each mapping constituting a regional model. After the analysis, the mapping of each process was generated and from it was compatibilized each mapping constituting a regional model. TOC was applied through the 5 steps: identifying, exploring, subordinating, elevating and returning to step 1, where it was possible to identify and analyze each constraint, to visualize a continuous improvement of this system and to propose a tool capable of mitigating the risks.